Volatile Organic Compounds (VOC) and Serum Leukotriene B4 between COPD Patients and COPD with Lung Cancer Patients - Susanthy Djajalaksana; Aditya Sri Listyoko; Kevin Wahyudy Prasetyo; Arinto Yudi Ponco Wardoyo (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is estimated to become the third leading cause of death worldwide in 2030. COPD can affect the lungs and cause chronic systemic inflammation. Leukotriene B4 (LTB4) is involved in COPD and lung cancer pathogenesis. There has been the development of non-invasive methods for detecting lung disease in the last few decades, such as the examination of volatile organic compounds (VOC). This study aimed to analyze the serum LTB4 and the difference of VOCs in exhaled breath of stable COPD patients and COPD with lung cancer patients. Methods: This case-control study recruited 20 stable COPD patients and 20 patients with COPD and lung cancer. An exhaled breath sample was collected in Tedlar bags and analyzed using an arrayed sensor breath analyzer to check the concentration of VOCs. Meanwhile, a venous blood sample was collected to examine the level of LTB4 using an ELISA kit. Independent t-test and Mann-Whitney test were used to analyze the data. Results: The carbon dioxide (CO2), nitrogen dioxide (NO2), carbon monoxide (CO), benzene (C6H6), and propane (C3H8) levels were significantly different (p <0.05) in COPD-only patients compared to COPD with lung cancer patients. Serum LTB4 increased in both groups. Conclusion: CO2, CO, and C3H8 levels increased, but the NO2 level decreased in COPD patients with lung cancer compared to COPD-only patients. Serum LTB4 increased in COPD with lung cancer patients.